2011
DOI: 10.4103/0301-4738.81029
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria and low hemoglobin as risk factors for the occurrence and increasing severity of diabetic retinopathy

Abstract: Aim:To assess the influence of urinary microalbuminuria and hemoglobin concentration on the occurrence and severity of diabetic retinopathy (DR), clinically significant macular edema (CSME) and hard exudate formation.Materials and Methods:In this prospective cross-sectional study carried out over a period of 2 years, type 2 diabetic patients seeking ocular evaluation for DR were assessed for presence and severity of DR, presence of hard exudates and CSME. Retinal findings were correlated to severity of microal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…The duration of diabetes is regarded as a marker for long-term exposure to hyperglycemia. Therefore, longer duration of diabetes may contribute the prevalence of DR. Lower hemoglobin levels were an independent predictor for the occurrence and severity of DR in the previous studies [21,25]. There is no clear evidence for the mechanism underlying the association of anemia with DR.…”
Section: Discussionmentioning
confidence: 80%
“…The duration of diabetes is regarded as a marker for long-term exposure to hyperglycemia. Therefore, longer duration of diabetes may contribute the prevalence of DR. Lower hemoglobin levels were an independent predictor for the occurrence and severity of DR in the previous studies [21,25]. There is no clear evidence for the mechanism underlying the association of anemia with DR.…”
Section: Discussionmentioning
confidence: 80%
“…Low hemoglobin has been described as an independent baseline risk factor in the EDTRS for the development of DME and severe visual loss [27]. Other studies have corroborated this finding [18] and have also found improvement in the DME status following correction of anemia [28-30]. Correction of anemia (and also supplementation of erythropoietin) was noted to decrease the effects of retinopathy with structural improvement, possibly through improved oxygenation of the macula [28].…”
Section: Discussionmentioning
confidence: 89%
“…In the MDRS 24-month cohort study, lower hemoglobin was associated with the presence of STDR at baseline (previously reported 14 ) but not with the progression of DR. Cross-sectional (but not cohort) studies have demonstrated an association between the presence of DR and anemia in India32, 33, 34 and China 35 . Potential confounders of the association between hemoglobin and retinopathy are socioeconomic and nutritional status and decreased erythropoietin production due to diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%